Cysteine Hydrochloride on Post-thawed Seminal Characters of Jersey Crossbred Bull - Perumal, P.; Selvaraju, S.; Barik, A. K.; Mohanty, D. N.; Das, S.; Mishra, P. C.; Veeraselvam, M. (International Journal of Bio-resource and Stress Management, 2012)
The role of cysteine hydrochloride in improving the post-thawed seminal characters in good and poor freezable Jersey crossbred bull semen was studied and compared with the control group. Two test groups, each containing 18 ejaculates, were studied in both good and poor freezable semen. The cysteine hydrochloride was added (5 mM) to the conventional Tris extender, fast freezing and followed by thawing and post-thawed seminal parameters were measured. Out these parameters the sperm viability, hypo-osmotic swelling, positive sperm, Vanguard distance travelled by sperm (mm h-1) in cervical mucus and nuclear fragmentation showed significant (p<0.05) difference between the two groups in both freezable bull semen, whereas the other parameters such as total motility and mitochondrial membrane potential were non-significantly higher and total sperm abnormality, loss of acrosomal integrity, malondialdehyde production were non-significantly lower in cysteine hydrochloride treated semen in both freezer. The addition of cysteine hydrochloride had maintained the functional parameters of good and enhances that in the poor freezable semen. Thus the cysteine hydrochloride improves post-thawed sperm functional parameters in poor freezable semen, suggesting that addition of cysteine hydrochloride in semen extender may improve fertility in these bulls.